Effect of endothelial microRNAs on blood pressure homeostasis - Satoshi Oikawa; Seiji Maeda; Takayuki Akimoto (Japanese Society of Physical Fitness and Sports Medicine, 2018)
Endothelial function is an important factor for maintenance of blood pressure (BP) homeostasis. Recently, microRNA (miRNA) has emerged as a potential regulator of endothelial function. However, the role of miRNAs in maintenance of BP homeostasis is unknown. In the present study, we investigated the potential role of endothelial miRNAs in BP regulation in vivo by using endothelial cell (EC)-specific Dicer knockout (KO) mice and measured BP before and after 8 weeks of high salt loading intervention. The EC-specific Dicer homozygous KO mice showed embryonic lethality. The EC-specific Dicer heterozygous KO mice (Het) showed a significant decrease in expression of Dicer mRNA in lung compared to wild-type (WT) mice. However, there were no differences between WT and Het mice in heart rates, systolic and diastolic blood pressures before and after 8 weeks of high salt loading. In this study, we demonstrated that the endothelial Dicer is essential for embryonic development. Additionally, we could not observe any phenotype in the hemodynamic parameters of EC-specific heterozygous Dicer KO mice.